The Student-Bloggers’ Voices on the Contribution of EFL Writing Through Blogging - Sari, Silvana Devinta (Widya Mandala Catholic University Surabaya, 2014)
Blogging is an effective way to help students write better as it positively enhances the students’ EFL writing skills. The following study is an attempt to evaluate student-bloggers’ opinions on blogging activity as it gives valuable contributions to student’s EFL writing skill. The research aimed at investigating student-bloggers’ attitudes towards the application of class blog in an informal learning situation. A descriptive case study was conducted to get more information on blogging contributions to student-bloggers’ EFL writing both for the process and the product of writing. The subjects were the student-bloggers of a language course whose blogging activity was intense. The data gathering was employed by probing interview and observation. Additionally, the thorough and meticulous analysis on the product of the writing was performed and scored using a rubric. Findings gathered from the interview depict the benefits and positive contributions of blogging to student-bloggers’ EFL writing. Blogging was certainly seen as a fun writing activity by the student-bloggers. It resulted from the fact that contrary to school learning, while blogging the students experienced autonomous learning, getting direct feedback from readers, and most importantly a complete freedom in writing. Some of blogging contributions for EFL writing are multi-literacy, direct feedback from readers, motivation, autonomous learning, critical thinking and language awareness, networking, freedom to write, and self confidence.